Mpox in Egypt: Status, preparedness and looming challenges - Zeiad Khedr; Mohamed Diab; Mohamad Khedr; Hala Mead; Yasmeen Mourad; Rehab El-Sokkary (Microbes and Infectious Diseases)
Background: Monkeypox (Mpox) is a zoonotic disease endemic in many countries of West and Central Africa with a trend of global spread due to its high contiguity. The emerging new clade of Monkeypox virus (MXPV), its swift spread in eastern the Democratic Republic of the Congo (DRC), and the reports of cases in several neighboring countries are alarming and worrisome. The World Health Organization (WHO) has recently declared Mpox as a public health emergency of international concern. In this narrative review, we present the microbiological features of MXPV, the status of Mpox, as well as the preparedness and the challenges that face the Egyptian health authorities. we concluded that while there are no current indications that the virus is headed towards Egypt, the interconnectedness of today’s world presents ongoing risks. To prevent the spread of the virus into Egypt, the Health Ministry has raised the alert level to the highest. However, with limited resources and competing healthcare demands, they face significant challenges. To address these vulnerabilities, it is recommended that Egyptian health authorities enhance early detection systems at key entry points, such as airports and border crossings, increase public awareness campaigns on Mpox, and establish emergency stockpiles of vaccines and antiviral treatments. Collaborative efforts with neighboring countries and international donors can also strengthen regional surveillance networks and improve Egypt's overall readiness to manage potential outbreaks.